Penentuan Parameter Titik-Titik Utama Siklus Kerja Mesin Diesel Kecepatan Tinggi Empat Langkah Dengan Perbandingan Kompresi 17 Dan Perbandingan Tekanan 1,8 (Kajian Teoritis) - Aloysius Eddy Liemena (Industrial Engineering Study Program, Pattimura University, 2012)
An internal-combustion engine is the name given to a reciprocating heat engine in which the fuel is burned directly inside a working cylinder. The mixture of gases produced upon the combustion of the fuel in the cylinder of the engine forms the working substance which presses against the piston and does work. The entire working cycle of a four-stroke engine is completed during four strokes of the piston or two revolutions of the crankshaft, with only one stroke of the piston being a working one. The shaft rotates during the other strokes at the expense of the work performed in other cylinders or of the reserve energy stored by the flywheel during the power stroke of the piston. The pressure and temperature at the principal points that characterize the working cycle of a diesel engine can be determined from formulas of thermodynamics with account taken of the thermochemical processes that take place in the engine. The result of determine the parameter is the pressure and temperature at the beginning of compression, pa= 0,90 kg/cm2and Ta= 310 K, pressure and temperature at the end of kompression, pc= 40,1 kg/cm2 and Tc= 812,3 K, and pressure and temperatuer at the end of combustion, pz=72,18 kg/cm2and Tz= 1984,12 K and pressure and temperature at the end of expansion, pb= 3,454 kg/cm2and Tb= 1135,5 K.